Pills or skills for hyperactive children. - O'Leary, K D (1980)
The controversial nature of drug treatment of hyperactivity, the incidence and sequelae of hyperactivity, and problems of differential diagnosis of hyperactivity versus aggression were discussed. The effects of psychostimulant medication and behavior therapy on hyperactive children were reviewed with regard to effects on their social and academic behavior. Both treatments have resulted in clear short-term changes in social behavior but neither long-term academic nor long-term social effects have been shown with either treatment. Short-term effects on academic behavior have resulted from behavioral interventions but not from psychostimulants. However, the interventions have been too brief to allow one to draw unequivocal conclusions about the clinical efficacy of behavioral treatments. Although there have been long-term evaluations of psychostimulant therapy, there have not been any evaluations of long-term behavioral treatment programs for hyperactive children. Given the salutary short-term effects of behavior therapy with hyperactive children, extended clinical trials of behavior therapy need to be conducted. Finally, specific directions are suggested for future research.